The Effects of Price And Service Quality on Customer Satisfaction at Alfamart Minimarket Betet Raya - Nunung Latipah; Lutfi Yudhaprawira; Cakra Wicaksono; Siti Maryana Ulfah; Uzrotul Muhaemin (Indonesian Development of Economics and Administration Journal, 2022)
The research was conducted on consumers of “Alfamart” Minimarket in Tangerang, with the research variables being price, service quality, and customer satisfaction. The purpose of this research is to analyze and test the truth of hypothesis about the effects of price and service quality on customer satisfaction at “Alfamart”. The study involved 96 respondents who were customers of “Alfamart”. The data was analyzed using validity test, classic assumption test, multiple linear regression equations, T-tests, F-tests, and Determination (R2). The results of hypothesis test is obtained conclusions are: There is a significant effect of price on customer satisfaction, it is proven with sig score = 0.000 < 0.05 and tCount > tTable, which is 9.310 > 1.985. There is a significant effect of service quality on customer satisfaction, it is proven with sig score = 0.000 < 0.05 and tCount > tTable, which is 7.520 > 1.985. There are simultaneously effects of price and service quality on customer satisfaction, it is proven with sig score = 0.000 < 0.05 and fCount > fTable, which is 52.027 > 3.09. The Adjusted R-Square value is 0.548.